CRYSTAL STRUCTURE REFINEMENT OF SAHLINITE, PB14(ASO4)2O9CL4 - Bonaccorsi E.; Pasero M. (My University, 2003)
The crystal structure of sahlinite [Pb14(AsO4)2O9Cl4] from Långban (Sweden) has been refined up to R = 0.071 using single-crystal diffraction data collected at the Elettra synchrotron facility. Sahlinite is monoclinic, space group C2/c, with a = 12.704(4), b = 22.576(5), c = 11.287(4) Å,  = 118.37(3)°. Sahlinite is isostructural with kombatite, its vanadium counterpart. Both are derivatives of the litharge form of PbO. In the structure of sahlinite there are seven independent Pb atoms, which are linked to Cl and/or O atoms, with coordination number ranging from V to VIII. The coordination polyhedra are irregularly shaped, due to the 6s2 lone-pair effect displayed by Pb2+.
Keywords: Sahlinite